Uczucia religijne a regulacja stosunków między małżonkami oraz między rodzicami i dziećmi - Jędrejek, Grzegorz (Ius Matrimoniale, 2008)
This article analyses the role o f religious feelings concerning the regulation of the relations between spouses and between parents and children. According to the author, the term “religious feelings” should be distinguished from the term “freedom of conscience and belief’ which belongs to the personal rights. The view that religious feelings are also the personal ights but of the subordinate nature must be rejected. The violation of religious feelings could be conceded as a reason for the breakdown o f marriage. Examining such violations, the subjective aspects should be taken into account. Parents are allowed to violate the personal rights of children connected with the religion when they are exercising their own rights deriving from parental authority or the right to upbringing children in a manner consistent with their own convictions. The unlawfulness of such actions is excluded because parents are acting in compliance with the law.